Comparison of current methods for anti‐dsDNA antibody detection and reshaping diagnostic strategies. (10th October 2022) - Infantino, Maria; Palterer, Boaz; Previtali, Giulia; Alessio, Maria‐Grazia; Villalta, Danilo; Carbone, Teresa; Platzgummer, Stefan; Paura, Giusi; Castiglione, Caterina; Fabris, Martina; Pesce, Giampaola; Porcelli, Brunetta; et al.
Abstract: Anti–double‐stranded DNA antibodies (anti‐dsDNA) are considered a specific marker for systemic lupus erythematosus (SLE). Though the Farr technique was once the reference method for their detection, it has been almost entirely replaced by more recently developed assays. However, there is still no solid evidence of the commutability of these methods in terms of diagnostic accuracy and their correlation with the Crithidia luciliae immunofluorescence test (CLIFT). Anti‐dsDNA antibody levels were measured in 80 subjects: 24 patients with SLE, 36 disease controls drawn from different autoimmune rheumatic diseases (14 systemic sclerosis, 10 Sjögren's syndrome, nine autoimmune myositis, three mixed connective tissue disease), 10 inflammatory arthritis and 10 apparently healthy blood donors by eight different methods: fluorescence enzyme immunoassay, microdot array, chemiluminescent immunoassay (two assays), multiplex flow immunoassay, particle multi‐analyte technology immunoassay and two CLIFT. At the recommended manufacturer cut‐off, the sensitivity varied from 67% to 92%, while the specificity ranged from 84% to 98%. Positive agreement among CLIFT and the other assays was higher than negative agreement. Mean agreement among methods assessed by the Cohen's kappa was 0.715, ranging from moderate (0.588) to almost perfect (0.888). Evaluation of the concordance among quantitative values by regression analysis showed a poor correlation index (mean r2, 0.66). The present study shows that current technologies for anti‐dsDNA antibody detection are not fully comparable. In particular, their different correlation with CLIFT influences their positioning in the diagnostic algorithm for SLE (either in association or sequentially). Considering the high intermethod variability, harmonization and commutability of anti‐dsDNA antibody testing remains an unachieved goal.